Integrating climate and nutrition risk planning for improved food and nutrition security in Mbale district - Okiror, John Francis; Muchunguzi, Perez (2019)
This info note summarizes findings of climate risk and nutrition profiling conducted by researchers from the International Institute of Tropical Agriculture (IITA) and International Center for Tropical Agriculture (CIAT) as part of a situation analysis for the second phase of the CCAFS project on Policy Action for Climate Change Adaptation (PACCA), which seeks to stimulate adoption of gender- and nutrition-sensitive climate-smart agriculture by aligning the national level agenda with implementation.